SAT0506 Ssc in older age: frequent and with a different phenotype. data of the german network for systemic sclerosis. (12th June 2018) - Moinzadeh, P.; Riemekasten, G.; Blank, N.; Henes, J.; Koetter, I.; Siegert, E.; Pfeiffer, C.; Zeidler, G.; Schmalzing, M.; Guenther, C.; Susok, L.; Worm, M.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a very heterogeneous multisystem connective tissue disease. The majority of affected patients develop initial clinical symptoms between the age of 30 to 50 years. It is not known whether an ageing population affects the clinical phenotype of SSc. Objectives: To investigate the relationship of the age at disease onset and clinical characteristics in SSc patients using the registry of the German Network for Systemic Scleroderma. Methods: Clinical data of the patient registry, currently including 4021 patients, were evaluated. Three age ranges at disease onset (<40 years, 40–60 years, and >60 years) were correlated with clinical characteristics. Results: Among all SSc patients, 27% of patients developed first non-raynaud symptoms at the age <40 years, while 44% developed SSc between 40–60 years, and 29% were older than 60 years of age. In particular, SSc patients with disease onset >60 years developed significantly (p<0.001) more often the lcSSc subtype (71.1%), anti-centromere antibodies (45.8%), had a significantly lower modified Rodnan Skin Score (mRSS) (7.8±8.1), more often pulmonary hypertension (PH) (17.4%), a significantly lower mean DLCO level (69.7%±21.5) and less often digital ulcerations (20.2%). However, a significant difference for lung fibrosis, heart or kidney involvement could not be observed. The more progressive subsets (dcSSc and SSc overlap syndromes) are found significantly more often at younger ages (p<0.001). Conclusions: In this registry, nearly one third of patients developed SSc at an age above 60 years. These are mostly of the limited cutanous subtype with frequent PH. These findings have an important influence on recommendations on diagnosis and theray of SSC. Disclosure of Interest: None declared